3D printable thermoplastic polyurethane blends with thermal energy storage/release capabilities. (June 2018) - Rigotti, D.; Dorigato, A.; Pegoretti, A.
Graphical abstract: Abstract: The aim of this work was to develope novel 3D printable thermoplastic polyurethane (TPU) blends with thermal energy storage (TES) capabilities. The target are potential applications for winter sport equipment. Different amounts of an encapsulated paraffin were added to a TPU matrix, and the resulting blends were then used to produce 3D printed samples. FESEM observation evidenced a homogeneous distribution of the capsules in the polymer matrix and a good adhesion between the layers in the 3D printed parts. DSC tests indicated that an effective energy storage/release capability was obtained in the 3D printed parts, with melting enthalpy values up to 70 J/g. The hard shells of the microcapsules, made of melamine formaldehyde resin, induced an increase of the stiffness, of the creep stability and of the Shore A hardness of the material, accompanied by a decrease of the elongation at break.